Hydroxyapatite formation on CaSiO3 ceramics in protein containing system - Okada, Kiyoshi; Siriphannon, Punnama; Kameshima, Yoshikazu; Yasumori, Atsuo; Hayashi, Shigeo (My University, 2001)
α-CaSiO3 ceramics with a nominal composition of CaO 46.0, SiO2 54.0, and Na2O 0.4 wt% were soaked in two different solutions, simulated body fluid (SBF) and α-minimum essential medium (α-MEM), to study the effect of protein on the formation of hydroxyapatite (HA). The SBF solution contained the same inorganic salts as in the human blood plasma, while the α-MEM solution contained both inorganic salts and various proteins. Both soaking systems were maintained at 36.5°C and a flow rate of about 40 ml/day for various periods of times. A complete coating of HA formed on the surface of the α-CaSiO3 ceramics in both solutions, but with different formation behavior and microstructure. The HA formed in the α-MEM system had ball-like particle morphology with a smaller particle size than the material formed in the SBF system. Cristobalite and/or unknown silicate phase coprecipitate with the HA in the α-MEM system but not in SBF. The HA layer formed on the ceramic surface achieved a thickness of about 80 and 93 μm after 20 days soaking in SBF and α-MEM solutions, respectively. The presence of protein in the α-MEM solution was considered to effect the microstructure of HA and possibly enhanced HA precipitation on the α-CaSiO3 ceramic. © 2002 Trans Tech Publications, Switzerland.
Keywords: Bioactive materials; Hydroxyapatite; Protein; α-casio3 ceramics